The role of riparian areas in alien plant invasions - Anđelković, Ana; Pavlović, Danijela; Radulović, Snežana (Acta herbologica, 2023)
Biological invasions represent one of the defining features of the Anthropocene, causing major problems and incurring significant economic losses worldwide, which are only projected to increase in the future. Riparian zones, as critical transition zones, despite providing numerous ecosystem services, are exposed to a multitude of human pressures, making them highly vulnerable to plant invasions. In fact, in Europe, riparian areas are considered to be among the most vulnerable habitat types. As foci of invasive plant species richness, they play an important role in the process of their spread into nearby terrestrial ecosystems. Various disturbance events, both natural (i.e. floods) and artificial (e.g. hydro-morphological alterations), in addition to a strong propagule pressure these areas are subjected to, increase the invasibility of these vulnerable zones. Given their ecological importance and susceptibility to plant invasions, the preservation and restoration of riparian zones is especially important in light of climate change. In order to preserve and restore the ecosystem services and biodiversity of riparian areas, invasive alien plants have to be managed. The success of restoration measures and control activities can be affected by many variables, such as the invasive plants' residence time and their legacy effects. Furthermore, different environmental factors and drivers of invasion must also be considered, as they could potentially impair the restoration measures. Finally, a successful restoration effort depends on the inclusion of all the relevant stakeholders and their understanding of the importance of preventing and managing plant invasions.
Keywords: invasive alien plants, riparian zone, invasibility, restoration